2018
DOI: 10.1002/14651858.cd012464.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Risk-reducing bilateral salpingo-oophorectomy in women with BRCA1 or BRCA2 mutations

Abstract: There is very low-certainty evidence that RRSO may increase overall survival and lower HGSC and breast cancer mortality for BRCA1 and BRCA2 carriers. Very low-certainty evidence suggests that RRSO reduces the risk of death from HGSC and breast cancer in women with BRCA1 mutations. Evidence for the effect of RRSO on HGSC and breast cancer in BRCA2 carriers was very uncertain due to low numbers. These results should be interpreted with caution due to questionable study designs, risk of bias profiles, and very lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
93
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(95 citation statements)
references
References 151 publications
1
93
0
1
Order By: Relevance
“…A prospective observational study showed that oophorectomy or salpingo-oophorectomy reduced the risk of OC by 80% [39]. A Cochrane meta-analysis including ten cohort studies and 8087 BRCA m carriers concluded with very-low certainty evidence that risk-reducing sapingo-oophorectomy reduces risk of death from OC [40]. A large cohort study found reduced risk of OC with tubal-ligation in BRCA 1/2 mutation carriers (HR, 0.43; 95% CI, 0.24–0.75; p = 0.003) [41].…”
Section: Introductionmentioning
confidence: 99%
“…A prospective observational study showed that oophorectomy or salpingo-oophorectomy reduced the risk of OC by 80% [39]. A Cochrane meta-analysis including ten cohort studies and 8087 BRCA m carriers concluded with very-low certainty evidence that risk-reducing sapingo-oophorectomy reduces risk of death from OC [40]. A large cohort study found reduced risk of OC with tubal-ligation in BRCA 1/2 mutation carriers (HR, 0.43; 95% CI, 0.24–0.75; p = 0.003) [41].…”
Section: Introductionmentioning
confidence: 99%
“…This difference may be the result of a “counselled risk”, based on the lower incidence and the slightly better prognosis of ovarian cancer in BRCA2 mutation carriers. However, a recent Cochrane review shows that BRCA carriers who received RRSO had longer overall survival, lower BC and OC mortality and better quality of life in term of OC risk perception [30]. Meta-analyses showed that RRSO might reduce the risk of death from OC and BC in BRCA1 carriers, but its role in BRCA2 carriers was uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…Current guidelines suggest that the assessment for cancer predisposition should be warranted only to those patients who are likely to have an inherited mutation, mainly based on personal or family history of BC or OR 11 , 17 .…”
Section: Introductionmentioning
confidence: 99%